Integration of Islamic Values in Stunting Prevention in Indonesia: Analysis of Surah An-Nisa' Verse 9 as the Foundation for a Holistic Approach Integrasi Nilai-Nilai Islam dalam Pencegahan Stunting di Indonesia: Analisis Surah An-Nisa' Ayat 9 sebagai Landasan Pendekatan Holistik - Ridwan, Ridwan; Faruq, Umar Al; Setyobudi, Teguh; Masykuroh, Ummi Farichatul; Fitriyah, Yusfa Nurul (Universitas Islam Negeri Raden Intan Lampung, 2024)
AbstractStunting is a serious global health challenge, especially in developing countries like Indonesia, where the prevalence is still high, around 30-40%. This condition not only affects children's physical growth, but also impacts cognitive development, academic achievement, and economic capabilities in adulthood, thereby contributing to a continuous cycle of poverty. Despite the implementation of various medical and nutritional interventions, stunting rates remain high, indicating the need for a more holistic and integrated approach. This research aims to examine the relevance and priority of Surah An-Nisa' Verse 9 in the context of stunting prevention in Indonesia with a focus on the integration of Islamic religious values in public health interventions. The method used was qualitative with a thematic interpretation approach, where data was obtained through a study of Al-Qur'an interpretation literature as well as interviews with health and religious experts in TK Darun Najah Kedemungan Village, Pasuruan City. The research results show that internalizing the values of Surah An-Nisa' Verse 9 can increase parents' awareness and responsibility for children's health and nutrition, which has significant potential in reducing the prevalence of stunting. In conclusion, integrating religious values in public health programs has great potential to strengthen the effectiveness of stunting prevention interventions, making them more culturally and spiritually relevant to Indonesian society. Keywords: Stunting, Surah An-Nisa' Verse 9, Internalization of Values, Public HealthAbstrakStunting merupakan tantangan kesehatan global yang serius, terutama di negara berkembang seperti Indonesia, di mana prevalensinya masih tinggi, yaitu sekitar 30-40%. Kondisi ini tidak hanya mempengaruhi pertumbuhan fisik anak, tetapi juga berdampak pada perkembangan kognitif, prestasi akademik, dan kemampuan ekonomi di masa dewasa, sehingga berkontribusi terhadap siklus kemiskinan yang berkelanjutan. Meskipun berbagai intervensi medis dan nutrisi telah diterapkan, angka stunting tetap tinggi, menunjukkan perlunya pendekatan yang lebih holistik dan terintegrasi. Penelitian ini bertujuan untuk mengkaji relevansi dan keutamaan Surah An-Nisa' Ayat 9 dalam konteks pencegahan stunting di Indonesia dengan fokus pada integrasi nilai-nilai agama Islam dalam intervensi kesehatan masyarakat. Metode yang digunakan adalah kualitatif dengan pendekatan tafsir tematik, di mana data diperoleh melalui studi literatur tafsir Al-Qur'an serta wawancara dengan pakar kesehatan dan agama di TK Darun Najah Kedemungan kota Pasuruan. Hasil penelitian menunjukkan bahwa internalisasi nilai-nilai dari Surah An-Nisa' Ayat 9 dapat meningkatkan kesadaran dan tanggung jawab orang tua terhadap kesehatan dan gizi anak, yang berpotensi signifikan dalam mengurangi prevalensi stunting. Kesimpulannya, integrasi nilai-nilai agama dalam program kesehatan masyarakat memiliki potensi besar untuk memperkuat efektivitas intervensi pencegahan stunting, menjadikannya lebih relevan secara kultural dan spiritual bagi masyarakat Indonesia.Kata kunci: Stunting, Surah An-Nisa' Ayat 9, Internalisasi Nilai, Kesehatan Masyarakat